A name for the glass catfish (Teleostei: Siluridae) revisited - Ng, Heok Hee; Kottelat, Maurice (Zootaxa, 2013)
We recently described a new species of catfish, Kryptopterus vitreolus (see Ng & Kottelat, 2013). Although the abstract, the introduction and the running title of that work made it clear that it was a new species, some may argue that the name is unavailable because it is not accompanied by the magic words ‘new species’. Article 16.1 of the International Code of Zoological Nomenclature (hereafter the Code) requires that in order to be available a new name “must be explicitly indicated as intentionally new”. Although our study explained that the species had no name and went on to provide a description and propose a name for it, we inadvertently omitted to accompany the name with the words “new species”, leaving room for argument that the name is technically unavailable in terms of Art. 16.1 of the Code.